Intestinal Microbiota as a Host Defense Mechanism to Infectious Threats - Iacob, Simona; Iacob, Diana Gabriela; Luminos, Luminita Monica (Frontiers in Microbiology, 2019)
Intestinal microbiota is a complex microbial community, with diverse and stable populations hosted by the gastrointestinal tract from birth. This ecosystem holds multiple anti-infectious, anti-inflammatory and immune modulating roles decisive for intestinal homeostasis. The antagonistic interactions between commensals and pathogenic flora are extremely dynamic and involve multiple mechanisms referred to as colonization resistance. Thus, gut bacteria compete for the same intestinal niches and substrates while also producing antimicrobial substances such as bacteriocines or changing the environmental conditions. Short chain fatty acids generated in anaerobic conditions prompt epigenetic regulatory mechanisms towards a tolerogenic immune response. In addition, comensal flora is involved in the synthesis of bactericidal products namely secondary biliary acids or antimicrobial peptides such as cathellicidin-LL37, an immunomodulatory, antimicrobial and wound healing peptide. Gut microbiota is protected through symbiotic relations with the hosting organism and by quorum sensing, a specific cell-to-cell communication system. Any alterations of these relationships favour the uncontrollable multiplication of the resident pathobionts or external entero-pathogens, prompting systemic translocations, inflammatory reactions or exacerbations of bacterial virulence mechanisms (T6SS, T3SS) and ultimately leading to gastrointestinal or systemic infections. The article describes the metabolic and immunological mechanisms through which the intestinal microbiota plays a protective role as an ally of the organism but also their limits that favour the development of infections.